The impact of parenting styles on children developmental outcome: The role of academic self‐concept as a mediator. (23rd August 2016) - Sangawi, Hoshiar; Adams, John; Reissland, Nadja
Abstract : Although the importance of parenting styles directly influencing child development is well established, fewer studied have examined whether parenting styles also affect children's behavioural problems indirectly, mediated through children's academic self‐concept (ASC). We examined direct and shared effects of parenting styles on behavioural problems of 199 Kurdish primary school children with a mean age of 11 years 7 months (range 11 years 5 months to 12 years 3 months). Questionnaires measured parenting styles (child version of Alabama Parenting Questionnaire), assessed children's ASC (Myself‐As‐Learner Scale) and identified children's behavioural problems with the Strengths and Difficulties Questionnaire (SDQ). PROCESS analysis was used to perform the mediation analysis. The results revealed that positive and negative parenting composites are indirectly related to children's internalising behaviour problems. In addition, ASC partially mediated the relationship between the negative parenting composite and prosocial behaviour. However, the mediation analysis did not show the expected indirect effect of parenting styles on externalising problems as being mediated via ASC. Hence, we argue that the ASC serves as a significant mediator in the relationship between parenting styles with prosocial behaviour and internalising problems.